2023
DOI: 10.3390/ph16091281
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Therapeutic Potential of Antimicrobial Peptides against Acinetobacter baumannii Infections

Karyne Rangel,
Guilherme Curty Lechuga,
David W. Provance
et al.

Abstract: The rise in antibiotic-resistant strains of clinically important pathogens is a major threat to global health. The World Health Organization (WHO) has recognized the urgent need to develop alternative treatments to address the growing list of priority pathogens. Antimicrobial peptides (AMPs) rank among the suggested options with proven activity and high potential to be developed into effective drugs. Many AMPs are naturally produced by living organisms protecting the host against pathogens as a part of their i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 320 publications
(328 reference statements)
0
5
0
Order By: Relevance
“…Medications that do not produce an excessive load on bacterial metabolism are less likely to induce resistance in the target bacteria ( Saipriya et al, 2020 ). Therapies for A. baumannii infections currently under development include immunotherapeutics ( Buchhorn de Freitas and Hartwig, 2022 ), photodynamic therapy ( Bustamante and Palavecino, 2023 ), subunit vaccine therapy ( Yang et al, 2022 ), phage therapy ( Tan et al, 2022 ), and antimicrobial peptide therapy ( Rangel et al, 2023 ). Research in other fields may also indirectly influence future A. baumannii treatments.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Medications that do not produce an excessive load on bacterial metabolism are less likely to induce resistance in the target bacteria ( Saipriya et al, 2020 ). Therapies for A. baumannii infections currently under development include immunotherapeutics ( Buchhorn de Freitas and Hartwig, 2022 ), photodynamic therapy ( Bustamante and Palavecino, 2023 ), subunit vaccine therapy ( Yang et al, 2022 ), phage therapy ( Tan et al, 2022 ), and antimicrobial peptide therapy ( Rangel et al, 2023 ). Research in other fields may also indirectly influence future A. baumannii treatments.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Among various biomolecules, antimicrobial peptides (AMPs) have been reported to display strong antibacterial activities. It is well documented in literature that antimicrobial peptides are positively charged peptides which further interact with the cell wall of bacteria via electrostatic interactions, which results in the breakage or damage of the bacterial wall morphology. A lot of reports have reported that a slight modification or immobilization of AMPs onto various types of material surfaces may preserve or even increase their biological properties. It has also been explored that incorporation of nanoparticles with biomolecules forms novel hybrid nano-biomaterials of synergetic properties and antimicrobial activity. , Zhao et al reported antimicrobial peptides conjugated with silver nanoparticles that were conjugated with a matrix metalloproteinase (MMP) cleavable sequence (PVGLIG), an antibacterial peptide (tachyplesin-1), and a target peptide (proline–glycine–proline (PGP)–polyethylene glycol (PEG)) . The developed system exhibited moderate antibacterial activity, but the system overall was quite complex.…”
Section: Introductionmentioning
confidence: 99%
“…For A. baumannii, due to its high antibiotic resistance and biofilm formation capacity, several natural AMPs and synthetic AMPs have been developed to replace conventional antibiotics, such as ZY4, Octominin, and Cec4 . However, the efficacy and toxic effects of newly developed antibiotic alternatives still need to be fully evaluated at the in vivo and in vitro levels to be suitable for clinical use.…”
Section: Introductionmentioning
confidence: 99%